Oxytocin Guidelines Associated with Compliance to National Standards. Issue 3 (May 2019) - Jackson, Jodi K.; Wickstrom, Elizabeth; Anderson, Betsi
Abstract: Objective: Develop a multidisciplinary, consensus-driven, evidence-based approach to oxytocin use, while adhering to national guidelines. Design: This was a quality improvement project that used the Plan Do Study Act method to create cycles of change over several years. To initiate discussion, a survey was administered at a social event for providers from divergent community practices that addressed the controversial aspects of oxytocin use. Graphic feedback was provided showing divergences between answers and the evidence. The perinatal team directed design and implementation of this project with specific involvement of a nurse quality improvement coordinator and nurse educator. Measures: Process, outcome, and balancing measures were used to evaluate the program. Process measure: use of a standardized order-set. Outcome measure: rate of adherence to the resultant protocol. Balancing measures: 1) maximum oxytocin dose, 2) time from oxytocin initiation to birth, 3) cesarean birth rates, and 4) Apgar scores. Results: An initial increase in adherence to the protocol decreased with the loss of the "paper" order-set. Adherence improved when computerized physician order entry was adjusted: 2006: 73%, 2007: 95%; 2011: 57%, 2013: 100% ( p = 0.007, 2006 vs. 2007) ( p < 0.001, 2006 vs. 2013). Compliance with the protocol was associated with a decrease in maximum oxytocin dose and in time between oxytocin initiation and birth ( p < 0.001). Conclusion: Consistency and safety in patient care can be accomplished using literature-based evidence and active consensus building among members of the perinatal team. A standardization process must be integrated into the electronic medical record to become a sustained part of a practice culture. Abstract : In this quality improvement project, a multidisciplinary team developed an evidence-based approach for use of oxytocin for induction and augmentation of labor based on a review of the literature, consensus building, and teamwork. Compliance with the standardized protocol was associated with a decrease in the maximum oxytocin dose and in the time between oxytocin initiation and birth. Fears of increasing the rate of cesarean birth due to a less aggressive method of using oxytocin were not found to be supported.